PENGARUH KEPATUHAN WAJIB PAJAK TERHADAP EFEKTIVITAS PENAGIHAN PAJAK BUMI DAN BANGUNAN DI KECAMATAN CIASEM KABUPATEN SUBANG - Hari Satia Nugraha; Eka Mulyani (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
This study aims to determine taxpayer compliance, to determine the effectiveness of land and building tax (PBB) collection, and to determine the effect of taxpayer compliance on the effectiveness of land and building tax (PBB) collection in Ciasem District, Subang Regency.This research uses a quantitative descriptive method and uses primary and secondary data. The sampling technique used was purposive sampling, namely a sampling technique with certain considerations, with a population of 39,118 WP. The samples taken were 100 respondents using the slovin formula. The data analysis method used is simple linear regression analysis with the help of SPSS 20.0 software for windows. Based on the results of testing the hypothesis obtained simple linear regression equation Y = -1.259 + 0.681 X + e, with a correlation value of R = 0.962 while the value of the coefficient of determination R2 = 0.926. The tcount value of taxpayer compliance is 34.932, while the fcount value is 1220.216. From the results of testing this hypothesis, it can be concluded that taxpayer compliance has a significant effect on the effectiveness of land and building tax collection in the Ciasem District of 0.926 or 92.6%, so that the influence of taxpayer compliance can contribute 92.6% to the effectiveness of land and building tax collection Building, the remaining 7.4% is influenced by other variables not examined.Keyword: Taxpayer Compliance, Effectiveness, Land and Building Tax Collection